Institutional Development of the Islamic Capital Market in Indonesia: Concepts, Instruments, and Regulatory Challenges - Yulia Fitriany Rahmah; Dedah Jubaedah; Muhammad Jagat Dermawan (PT. Student Rihlah Indonesia, 2026)
The Islamic capital market constitutes an essential component of the Islamic financial system, designed to provide investment mechanisms that comply with Sharia principles, particularly the prohibition of riba, gharar, and maisir. This study aims to examine the concept, institutional structure, instruments, economic functions, as well as the challenges and development strategies of the Islamic capital market in Indonesia. The research employs a qualitative descriptive approach with conceptual and normative analysis, based on a literature review of regulatory frameworks, fatwas issued by the National Sharia Council of Indonesia, and relevant academic and institutional publications. The findings indicate that the Islamic capital market in Indonesia has established a relatively sound conceptual and regulatory foundation through the integration of national capital market law and Sharia governance. The main instruments include Sharia-compliant equities, sukuk, and Islamic mutual funds, with the Jakarta Islamic Index serving as a benchmark for Sharia-based equity performance. Nevertheless, the development of the Islamic capital market remains constrained by limited investor literacy, shallow market depth, and the absence of a dedicated Islamic capital market law. This study highlights the need for strengthening the regulatory framework, expanding product innovation, and enhancing market literacy to maximize the contribution of the Islamic capital market to sustainable national economic development.